Strategic management : a competitive advantage approach, concepts and cases / Fred R. David, Forest R. David - David, Fred R.
PART 1: OVERVIEW OF STRATEGIC MANAGEMENT 1. The Nature of Strategic Management PART 2: STRATEGY FORMULATION 2. Business Vision and Mission 3. The External Assessment 4. The Internal Assessment 5. Strategies in Action 6. Strategy Analysis and Choice PART 3: STRATEGY IMPLEMENTATION 7. Implementing Strategies: Management and Marketing Issues 8. Implementing Strategies: Finance and Accounting Issues PART 4: STRATEGY EVALUATION AND GOVERNANCE 9. Strategy Evaluation and Governance \ PART 5: KEY STRATEGIC MANAGEMENT TOPICS 10. Business Ethics, Environmental Sustainability, and Corporate Social Responsibility 11. Global and International Issues PART 6: STRATEGIC MANAGEMENT CASE ANALYSIS How to Prepare and Present a Case Analysis